Building Bioethics
IX, 254 p. 2 illus.
Keywords: K. Danner Clouser is one of the most important figures in establishing and shaping the fields of medical ethics, bioethics, and the philosophy of education in the second half of the twentieth century. Clouser challenged many established approaches to moral theory and offered innovative strategies for integrating the humanities into professional education, especially that of physicians and nurses. The contributions published in Building Bioethics: Conversations with Clouser and Friends on Medical Ethics are unique both in their devotion to a critical review of his contributions, and in bringing together internationally known figures in bioethics, medical ethics, and philosophy of medicine to comment upon Clouser's work. These leaders of the field include Tom Beauchamp, Daniel Callahan, James Childress, Nancy Dubler, H. Tristram Engelhardt, Al Jonsen, Loretta Kopelman, Larry McCullough, John Moskop, and Robert Veatch. This book merits special attention from those interested in bioethics, philosophy of medicine, medical ethics, philosophy, medical education, religious studies, and nursing education.